PRODUCTION OF CYCLODEXTRIN GLYCOSYL TRANSFERASE FROM ALKALIPHILIC Paenibacillus sp L55 MCM B - 1034 ISOLATED FROM ALKALINE LONAR LAKE, INDIA - REBECCA S.THOMBRE; PRADNYA P. KANEKAR; J.M.RAJWADE (International Journal of Pharma and Bio Sciences, 2013)
Cyclodextrin glycosyl transferase (CGTase; EC 2.4.1.19) is an enzyme which converts starch into cyclodextrins (CDs). Cyclodextrins are closed-ring structures in which six or more glucose units are joined by α-1, 4 glucosidic bonds. Cyclodextrins have applications in food, pharmaceutical and cosmetic industries. This paper reports the exploration of aerobic alkaliphilic bacteria from alkaline soda lake of Lonar, India for CGTase production. Paenibacillus sp L55 isolated from Lonar lake was used for production of CGTase. Three medium components Starch, Peptone and Yeast extract and initial pH of medium were optimised by Taguchi Design of Experiments (DOE). The contribution of starch in CGTase production was the highest while pH showed the least contribution in CGTase production. The optimised medium was used for CGTase production and the yield of CGTase was increased from 3 U/ml to 5.1 U/ml.